AI Speaks Your Language: Measuring ChatGPT's Impact on English Proficiency and Student Engagement in Higher Education - Riojas Rivera, Jimmy Ronald; Mejia De Paz, Octavio David; PANTA CHUNGA, MARY INOCENCIA; Duran Herrera, Víctor Hugo; NIEVES BARRETO, CONSTANTINO MIGUEL; DURAND GONZALES, CESAR ANGEL; ALEJOS IPANAQUÉ, RUFINO (LACCEI, 2025)
The integration of Artificial Intelligence (AI) in language education is transforming traditional teaching methodologies. This quasi-experimental study examines the impact of ChatGPT on the motivation, engagement, and proficiency of undergraduate students learning English at the A1 level. A total of 290 students from Law and Business Administration programs at Universidad Privada del Norte participated in a 12-week AI-enhanced curriculum. Pre-test and post-test results were analysed alongside student perceptions collected through surveys. Findings indicate that while students reported increased motivation and engagement, statistical analysis showed no significant improvement in test scores. ChatGPT was particularly valued for its feedback and vocabulary-building capabilities but was less effective in enhancing pronunciation. These results suggest that AI tools like ChatGPT can serve as valuable supplements to language instruction, especially when combined with specialized resources for speaking and pronunciation, such as THINKLING. The study highlights the need for continued exploration of AI-driven learning methodologies to optimize their impact on language acquisition.